Front Cover: The Application of HEXS and HERFD XANES for Accurate Structural Characterisation of Actinide Nanomaterials: The Case of ThO2 (Chem. Eur. J. 1/2021). Issue 1 (18th November 2020) - Amidani, Lucia; Vaughan, Gavin B. M.; Plakhova, Tatiana V.; Romanchuk, Anna Yu.; Gerber, Evgeny; Svetogorov, Roman; Weiss, Stephan; Joly, Yves; Kalmykov, Stepan N.; Kvashnina, Kristina O.
Abstract : Oh, now I see ! The precipitates formed during Th IV hydrolysis are ThO2 nanoparticles, which in their initial stages of formation are a mixture of ultra‐small nanoparticles and Th hexamer clusters. This new structural insight is made possible by the combined use of two synchrotron techniques: HEXS and XANES in HERFD mode, which probe short‐ and medium‐range order in the sample under study. More information can be found in the Full Paper by L. Amidani et al. on page 252 .